(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: In various scenarios, precision and form stability of 3D printed structures are of major importance. As an example, the material has to carry mechanical load or must sustain thermal stress. If the material’s surrounding is predominantly wet or if the material functions as a repository containing some liquid the ability of absorbing fluids matters. For these reasons, there is a high interest in investigated certain material parameters of a specific 3D printer that is used. Materials and Methods: Different models were created by a 3D printer using the additive manufacturing process based on photopolymerization. Under different environmental circumstances like temperature, pressure and storage conditions, parameters as the size- and form stability are investigated and quantified. Model properties like the wall thickness are varied to examine their influence on the results. Furthermore, the water absorptive capacity is quantified and a coating is applied to study its effect. Results and Discussion: In the scope of this work, slight deviations between the modelled and the printed objects can be assessed according the height whereas the width reveals a high accuracy. The size of the objects correlates with the temperature in a proportional manner. The material’s ability to absorb water can be neglected in most cases, when very low amounts of absorption of liquid are no critical factor. Conclusion: Several 3D-printed models were constructed to evaluate their properties. It could be shown that it is advisable to compensate for the height of the model due to deviations. Besides, a change in size due to significant temperature fluctuations has to be taken into account according to the field of use or environmental circumstances. Using coating for further decrease of the water absorption, a sophisticated surface treatment appears to be necessary.